Mapping and quantifying nascent transcript start sites using TT-TSS-seq - Elgood Hunt, Eleanor; Vivori, Claudia; Mitter, Richard; Agnadottir, Vedis; van Werven, Folkert J. (Genome Research, 2026)
Transcription initiation is a highly dynamic and tightly regulated process involving the coordinated action of transcription factors, chromatin remodelers, and RNA polymerase, which determine where and when transcription begins. Accurately mapping and quantifying transcription start sites (TSSs) from nascently transcribed RNAs remains a key area of interest, as it provides critical insights into transcription dynamics. Here, we combine transient transcriptome sequencing with transcription start site sequencing (TT-TSS-seq) to accurately map and quantify transcription initiation sites from nascent transcripts. Because transient metabolic labeling yields low-input RNA, we optimize the TSS-seq protocol to enhance sensitivity and accuracy. Specifically, we refine enzymatic reactions for decapping and RNA ligation and incorporate 5′ oligonucleotides containing unique molecular identifiers (UMIs) and barcodes to enable accurate quantification and sample multiplexing. The TT-TSS-seq approach detects transcription initiation of unstable transcripts, such as enhancer RNAs. Moreover, we show that a large fraction of genes use multiple transcription initiation sites, yet often produce only a single stable transcript. Overall, TT-TSS-seq provides precise mapping and quantification of transcription initiation sites, offering new insights into transcriptional dynamics and expanding the toolkit for studying gene regulation.
10.1101/gr.280726.125